Head Computed Tomography Images of HIV/AIDS Patients with Suspected Cerebral Toxoplasmosis in Dr. Soetomo General Hospital Surabaya - Ria Wibawani; Bambang Soeprijanto; Widiana Ferriastuti; Erwin A Triyono (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: Toxoplasma gondii is an intracellular pathogenic parasite with the majority of co-infections occurring in HIV/AIDS patients. This study assesses the head computed tomography (CT) images of cerebral toxoplasmosis in patients with HIV/AIDS.Methods: This study was a cross-sectional design using head CT images of 35 HIV/AIDS patients with suspected cerebral toxoplasmosis. Variables include lesion type, location, size, CD4 count, and therapeutic result with anti-cerebral toxoplasmosis. All data analysed descriptively.Results: From total 110, 35 patients met the inclusion criteria. 24 patients (68.6%) were male and 11 (31.4%) female, average age, was 36.1. 8 patients (22.3%) had lesions in cortical, 31 patients (88.6%) had < 1 cm lesion. Single lesions mainly calcified and found in the right centrum semiovale while multiple lesions were subcortical. A hypodense lesion with rim or nodular contrast enhancement is found in 75% of patients with CD4 > 200 in contrast to slight rim contrast enhancement and perifocal edema in patients with CD4 < 200. 20 patients (57.4%) had improved condition after anti-toxoplasmosis therapy.Conclusion: Cerebral toxoplasmosis lesions in HIV/AIDS patients have various types of imaging findings, mostly multiple, with most frequent location being cortical and diameter < 1 cm. Total recovery is achieved in the majority of patients with therapy.